Guppies learn faster to discriminate between red and yellow than between two shapes - Lucon‐Xiccato, Tyrone; Manabe, Kazuchika; Bisazza, Angelo; Wright, J. (Ethology, 2019)
Animal species are expected to evolve specialised cognitive abilities to solve the tasks that are critical for their fitness. The literature contains several examples of specialised cognitive abilities, but few regard fish. The guppy, Poecilia reticulata, is a freshwater fish in which females choose their mates based on colouration, and orange‐coloured fruits are important diet enrichments for both sexes. For these reasons, we expect that this species has evolved enhanced learning abilities in colour discrimination compared to other types of discrimination. The comparison between studies in which guppies were tested for colour discrimination and studies in which guppies were tested for shape discrimination seems to support this hypothesis, but direct testing is still lacking. We experimentally compared the learning performance of guppies trained in a red–yellow colour discrimination learning task and that of guppies trained in a shape discrimination learning task using the same, automated conditioning procedure. Guppies trained in the colour discrimination showed greater learning performance, which provides support to the hypothesis that guppies possess enhanced colour discrimination abilities. Moreover, we found that male guppies performed better than females in both shape and colour discrimination learning.